Study of preferential display method of a cultural museum in Bandung, Indonesia - Krismanto Kusbiantoro; Irena Vanessa Gunawan; Tantri Oktavia; Astrid Austranti Yuwono (ARTEKS : Jurnal Teknik Arsitektur, 2022)
Museums have an important role in preserving the journey of a nation. Museum records prove or evidence of the journey, like culture, language, politics amongst many other things. The success of museums to deliver information and communicate the content to museum visitors and other users rely on a strategic display method. There are many categories of museum objects, each has its story to tell. However, the method to display this fast information has limitations, usually regarding the availability of physical space. Hence, study is needed to help museum designers or administrators determine which method is an optimum solution to deliver the information to the visitor. Therefore, it is the intention of this research to conduct study through survey to museum visitors or users of their preferred basic approach of display methods which are aesthetic, intellectual or thematic. The method used for this research is visual research method. The visitor’s perception about the preferential method of display is extracted using a visual questionnaire followed by a structured interview. The research found that the 3-basic approach of display is vast depending on the categories of the object exhibits. History category is preferred to be displayed in an intellectual display approach, while as fashion, festival, language, music, artefact and influential people/figures categories, they are preferred to be displayed using the aesthetic approach. Thematic display approach is considered effective to present the object of food, dance and architecture category. The result of the research is then developed into proposed display design as a reference for museum designer or administrator to display objects effectively.